Climate-Driven Alterations in the Mercury Cycle: Implications for Wildlife Managers Through a One Health Lens - Jennifer L. Wilkening; Angelika L. Kurthen; Kelly Guilbeau; Dominic A. Libera; Sarah J. Nelson; Jaron Ming (Land)
Mercury (Hg) is a naturally occurring element, but atmospheric Hg has increased due to human activities since the industrial revolution. When deposited in aquatic environments, atmospheric Hg can be converted to methyl mercury (MeHg), which bioaccumulates in ecosystems and can cause neurologic and endocrine disruption in high quantities. While higher atmospheric Hg levels do not always translate to higher contamination in wildlife, museum specimens over the past 2 centuries have documented an increase in species that feed at higher trophic levels. Increased exposure to pollutants presents an additional threat to fish and wildlife populations already facing habitat loss or degradation due to global change. Additionally, Hg cycling and bioaccumulation are primarily driven by geophysical, ecological, and biogeochemical processes in the environment, all of which may be modulated by climate change. In this review, we begin by describing where, when, and how the Hg cycle may be altered by climate change and how this may impact wildlife exposure to MeHg. Next, we summarize the already observed physiological effects of increased MeHg exposure to wildlife and identify future climate change vulnerabilities. We illustrate the implications for wildlife managers through a case study and conclude by suggesting key areas for management action to mitigate harmful effects and conserve wildlife and habitats amid global change.